A One-Health Approach to Investigating an Outbreak of Alimentary Tick-Borne Encephalitis in a Non-endemic Area in France (Ain, Eastern France): A Longitudinal Serological Study in Livestock, Detection in Ticks, and the First Tick-Borne Encephalitis Virus Isolation and Molecular Characterisation - Gonzalez, Gaëlle; Bournez, Laure; Moraes, Rayane Amaral; Marine, Dumarest; Galon, Clémence; Vorimore, Fabien; Cochin, Maxime; Nougairède, Antoine; Hennechart-Collette, Catherine; Perelle, Sylvie; Leparc-Goffart, Isabelle; Durand, Guillaume André; et al. (Frontiers in Microbiology, 2022)
Tick borne encephalitis virus geographic range and human incidence is increasing throughout Europe, putting a number of non-endemic regions and countries at risk of outbreaks. In spring 2020, there was an outbreak of TBE in Ain, Eastern France, where the virus had never been detected before. All patients but one had consumed traditional unpasteurized raw goat cheese from a local producer. We conducted an investigation in the suspected farm using an integrative One Health approach. Our methodology included (i) the detection of virus in cheese and milk products, (ii) serological testing of all animals in the suspected farm and surrounding farms, (iii) an analysis of the landscape and localisation of wooded area, (iv) the capture of questing ticks and small mammals for virus detection and estimating enzootic hazard, and (v) virus isolation and genome sequencing. This approach allowed us to confirm the alimentary origin of the TBE outbreak and to witness in real time the seroconversion of recently exposed individuals and the excretion of virus in goat milk. In addition, we identified a wooded focus area where and around which there is a risk of TBEV exposure. We provide the first TBEV isolate responsible for as a source of dietary contamination in France, obtained its full-length genome sequence, and found that it does not cluster very closely neither with the isolate circulating in Alsace nor with any other isolate within the European lineage. TBEV is now a notifiable human disease in France, which should facilitate surveillance of TBEV incidence and distribution throughout France.